ANALYSIS OF PERFORMANCE IMPROVEMENT AT THE AMBARITA FERRY PORT IN SAMOSIR REGENCY - MARIA, FIRDA; TAMPUBOLON, FREDDY (IWTJ : International Water Transport Journal, 2025)
Optimal port performance can only be achieved through the support of facilities, human resources, and service systems that meet the needs of port service. The Ambarita Ferry Port is a strategic transportation hub in Samosir Regency that serves the Ambarita–Ajibata route, which has experienced significant growth in recent years. During the 2020–2024 period, the number of passengers increased by 117.61% and vehicles by 73.36%. However, this growth has not been matched by adequate service facilities, such as limited waiting areas, inadequate safety facilities, limited access to information, and the absence of a port zoning system. In this research, an in-depth analysis is carried out to understand the effectiveness of the service and develop strategies to enhance the performance of the port. The results of the performance evaluation indicate that there is still a gap between The importance and performance of the service. An assessment using The Importance Performance Analysis (IPA) method is used to assess the relative importance of factors in a given context indicates that the overall service performance conformity level is 59.33%, falling into the moderate category, with some service indicators in quadrants I to IV. Recommendations for improvement include the provision of protective facilities (signage), service information (maps/facility locations, fares, and onward transportation), and the reorganization of parking areas and terminals. The five-year demand projection (2025–2029) is estimated to reach 1,070,144 passengers and 213,532 mixed vehicles.